Pendidikan Islam dan Kesesuaian Nilai Hidup dengan Surat Al-Maidah Ayat 36: Sebuah Kajian Tematis - Muhammad Khairul Amri; Sucipto Sucipto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to analyze the alignment of life values contained in Surah Al-Maidah, verse 36, with the objectives of Islamic education. The verse teaches the importance of moral accountability, sincerity in repentance, and spiritual awareness, which can be applied in the learning process to shape students' character. The method used is a qualitative approach with thematic analysis of relevant tafsir and literature related to the research theme. The findings indicate that the values in Surah Al-Maidah, verse 36, are highly relevant to the principles of Islamic education, which emphasize the formation of noble character, social responsibility, and spiritual awareness. The implication of these findings is the importance of integrating these values into the Islamic education curriculum so that education focuses not only on intellectual aspects but also on shaping students' character with good morals and high spiritual awareness.